CONTRIBUTION OF SOCIAL MEDIA AND GREEN MARKETING IN IMPROVING PURCHASING DECISIONS AT MCDONALD WILLIAM ISKANDAR - Situmorang, Irvan Rolyesh; Wilbert, Wilbert (JURNAL MUTIARA MANAJEMEN, 2025)
The rapid development of the era into the digital era makes competition in the business world increasingly tight. Companies must be able to determine the right marketing strategy to get maximum profit, the use of social media and green marketing strategies are one of the most widely used methods today. Therefore, this consideration aims to determine the impact of social media and green marketing on purchasing choices at McDonald William Iskandar Medan. The r strategy used in this study is quantitative, and the population used in this study consists of customers who have shopped at McDonald William Iskandar Medan, the exact number of which cannot be determined. Because the number of respondents is uncertain, the researcher uses the hair method, which can be a strategy used when the researcher does not know the exact population estimate. In this study, 110 respondents were obtained, while the testing procedure used was a coincidence test. Data testing includes the classical expressive assumption test, different direct testing, fractional theory test (t-test) and simultaneous test (f-test), and the confidence coefficient test. This study produces a positive critical impact, both partially and simultaneously, between social media and green marketing on purchasing choices at McDonald William Iskandar Medan.